From soft to hard magnetic Fe–Co–B by spontaneous strain: a combined first principles and thin film study. (9th November 2015) - Reichel, L; Schultz, L; Pohl, D; Oswald, S; Fähler, S; Werwiński, M; Edström, A; Delczeg-Czirjak, E K; Rusz, J
Abstract: In order to convert the well-known Fe–Co–B alloy from a soft to a hard magnet, we propose tetragonal strain by interstitial boron. Density functional theory reveals that when B atoms occupy octahedral interstitial sites, the bcc Fe–Co lattice is strained spontaneously. Such highly distorted Fe–Co is predicted to reach a strong magnetocrystalline anisotropy which may compete with shape anisotropy. To probe this theoretical suggestion experimentally, epitaxial films are examined. A spontaneous strain up to 5% lattice distortion is obtained for B content up to 4 at%, which leads to uniaxial anisotropy constants exceeding 0.5 MJ m −3 . However, a further addition of B results in a partial amorphisation, which degrades both anisotropy and magnetisation.